2006
DOI: 10.1002/smi.1125
|View full text |Cite
|
Sign up to set email alerts
|

Daily hassles and depressive symptoms among first year psychology students in France: the role of coping and social support

Abstract: The start of university life demands an adaptation period, which can sometimes have an impact on the mental health of students. A total of 233 first year psychology students answered a questionnaire based on a Beck Depression Inventory, Coping Inventory of Stressful Situations, Social Support Questionnaire and Hassles Scale. The results showed 41 per cent of those surveyed suffered of depressive symptoms and that daily hassles encountered during the first year of university could be considered a relevant risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
2
22

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 34 publications
7
74
2
22
Order By: Relevance
“…Schafer (1996) observed that the most stressful daily hassles reported by college students were school-related, including writing term papers, taking tests, and the constant pressure of studying. For many students the end results of these stressors are elevated levels of anxiety and depression (Bouteyre, Maurel, & Bernaud, 2007), more frequent incidents of illness (Lesko & Summerfield, 1989), poorer academic performance (Struthers, Perry, & Menec, 2000), or departure from academia (Daugherty & Lane, 1999).…”
mentioning
confidence: 99%
“…Schafer (1996) observed that the most stressful daily hassles reported by college students were school-related, including writing term papers, taking tests, and the constant pressure of studying. For many students the end results of these stressors are elevated levels of anxiety and depression (Bouteyre, Maurel, & Bernaud, 2007), more frequent incidents of illness (Lesko & Summerfield, 1989), poorer academic performance (Struthers, Perry, & Menec, 2000), or departure from academia (Daugherty & Lane, 1999).…”
mentioning
confidence: 99%
“…A variety of coping strategies have been identified, both adaptive and maladaptive. 3,4,[14][15][16] For adolescents and college students, the use of active and internal coping strategies (adaptive coping) such as direct problem-solving, positive thinking, leisure activities, and humor have been related to positive affect and well-being. Conversely, the use of avoidant coping strategies (maladaptive coping) such as withdrawal and avoidance has been associated with negative affect, distress, and decreased emotional and psychological well-being.…”
mentioning
confidence: 99%
“…Frequencies and percentages for the prevalence rates were based on T-scores. The two subscales of the avoidance coping orientation (distraction and social diversion) were not scored and analyzed separately in this study because they inter-correlate positively and strongly (see Bouteyre et al, 2007).…”
Section: Discussionmentioning
confidence: 99%